2019
DOI: 10.1038/s41467-019-09373-w
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing of canids reveals genomic regions under selection and variants influencing morphology

Abstract: Domestic dog breeds are characterized by an unrivaled diversity of morphologic traits and breed-associated behaviors resulting from human selective pressures. To identify the genetic underpinnings of such traits, we analyze 722 canine whole genome sequences (WGS), documenting over 91 million single nucleotide and small indels, creating a large catalog of genomic variation for a companion animal species. We undertake both selective sweep analyses and genome wide association studies (GWAS) inclusive of over 144 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
419
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(434 citation statements)
references
References 76 publications
13
419
2
Order By: Relevance
“…This is the first report of the tan point ( ASIP ), and long hair ( FGF5 ) variants in wild canine populations. A recent paper verified the CFA10 ear shape locus, and demonstrated that, while definitively a contributing locus, it does not perfectly account for ear phenotype (28). Thus, the higher frequency of ear shape and hair length variant alleles in wild populations is perhaps not surprising, as these phenotypes are known to be driven by more than one locus (20,27,54).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report of the tan point ( ASIP ), and long hair ( FGF5 ) variants in wild canine populations. A recent paper verified the CFA10 ear shape locus, and demonstrated that, while definitively a contributing locus, it does not perfectly account for ear phenotype (28). Thus, the higher frequency of ear shape and hair length variant alleles in wild populations is perhaps not surprising, as these phenotypes are known to be driven by more than one locus (20,27,54).…”
Section: Discussionmentioning
confidence: 99%
“…To predict the functional effects of the called variants, SnpEff [26] software together with NCBI annotation release 105 for the CanFam 3.1 genome reference assembly was used. For variant filtering we used 654 control genomes, which were either publicly available [27,28] or produced during other projects of our group [24] (Table S4).…”
Section: Variant Callingmentioning
confidence: 99%
“…To predict the functional effects of the called variants, SnpEff [11] software together with NCBI annotation release 105 for the CanFam 3.1 genome reference assembly was used. We used a vcf-file containing 648 dog and 8 wolf genomes, which were either publicly available [12,13] or produced during other projects of our group [10]. We excluded 10 genome sequences from other Belgian Shepherd dogs from filtering to minimize the risk of having any unrecognized carriers in the control cohort.…”
Section: Variant Calling and Filteringmentioning
confidence: 99%